The people of Cuth made Nergal (2 Kings 17:30).The historicity and cult of Nergal in the Ancient Middle East. - Rasztawicki, Leszek (Warszawskie Studia Teologiczne, 2019)
In this paper we would like to investigate the historicity of Nergal of Cuth in the context of Mesopotamian literature and religion. The deity Nergal of Cuth appears only once in the Hebrew Bible (2 Kings 17:30). He is mentioned among a list of some Assyrian gods, which new repopulated settlers in Samaria “made” for themselves after the fall of the Northern Kingdom. He is mainly perceived as a god of war and pestilence and his name can be explained “the lord of the netherworld”. His cult is mentioned in a prosaic way in the Hebrew Bible. On the other hand, there are many hymns and written texts, praising his glory and might, which support the existing cult of Nergal. His cult is further attested in Greek and Roman cultures.